Long-term follow-up and treatment in nine boys with X-linked creatine transporter defect - van de Kamp, Jiddeke M. (Springer Netherlands, 2011)
The creatine transporter (CRTR) defect is a recently discovered cause of X-linked intellectual disability for which treatment options have been explored. Creatine monotherapy has not proved effective, and the effect of treatment with L-arginine is still controversial. Nine boys between 8 months and 10 years old with molecularly confirmed CRTR defect were followed with repeated (1)H-MRS and neuropsychological assessments during 4–6 years of combination treatment with creatine monohydrate, L-arginine, and glycine. Treatment did not lead to a significant increase in cerebral creatine content as observed with H(1)-MRS. After an initial improvement in locomotor and personal-social IQ subscales, no lasting clinical improvement was recorded. Additionally, we noticed an age-related decline in IQ subscales in boys affected with the CRTR defect.